Accessibility of Universal Postal Service According to Access Points Density Criteria: Case Study of Bjelovar-Bilogora County, Croatia - Mostarac, Katarina; Kavran, Zvonko; Rakić, Estera (Promet - Traffic&Transportation, 2019)
Universal service providers have an obligation to provide a minimum required set of postal services – known as universal service obligation. To ensure universal service obligation, regulatory measures (criteria) which service providers must fulfil are often set up. In this paper, a geographical analysis of these criteria is conducted using current regulatory framework in the Republic of Croatia as an example. Based on the framework of the gravity model, accessibility of postal service is presented. The goal of the proposed research is to investigate the application of the gravity model for determining postal service accessibility, with special emphasis on rural areas. To our knowledge, this method has not been used in previous studies to determine accessibility of postal services. The results of the applied model could be used in future planning of access density criteria with various transportation modes.